2017
DOI: 10.1371/journal.pcbi.1005618
|View full text |Cite
|
Sign up to set email alerts
|

Flux balance analysis predicts Warburg-like effects of mouse hepatocyte deficient in miR-122a

Abstract: The liver is a vital organ involving in various major metabolic functions in human body. MicroRNA-122 (miR-122) plays an important role in the regulation of liver metabolism, but its intrinsic physiological functions require further clarification. This study integrated the genome-scale metabolic model of hepatocytes and mouse experimental data with germline deletion of Mir122a (Mir122a–/–) to infer Warburg-like effects. Elevated expression of MiR-122a target genes in Mir122a–/–mice, especially those encoding f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 59 publications
1
27
0
Order By: Relevance
“…The function of miR-122a has been reported in several human diseases (12)(13)(14)(15). It has been shown that miR-122a is likely involved in Warburg-like effects of hepatocyte deficient in mice (12).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The function of miR-122a has been reported in several human diseases (12)(13)(14)(15). It has been shown that miR-122a is likely involved in Warburg-like effects of hepatocyte deficient in mice (12).…”
Section: Discussionmentioning
confidence: 99%
“…However, the involvement of MANCR in HCC is unknown. MicroRNA (miR)-122a is a key player in a number of types of diseases including HCC (12)(13)(14)(15)(16). miR-122a is downregulated in HCC and predicted poor survival (16).…”
Section: Introductionmentioning
confidence: 99%
“…Limited to transciptomic processes, ignoring metabolic and proteomic regulation Whole-cell metabolic network modeling (Aguilar et al, 2016;Tsai et al, 2009;Wu et al, 2017): Flux balance and constraint-based reconstruction and analysis (COBRA) (Becker et al, 2007) Able to integrate metabolomic and genomic data…”
Section: Computational Techniquesmentioning
confidence: 99%
“…Wu et al [21] developed a CBM based on the published Recon 2 and the Warburg effects of mouse hepatocytes deficient in miR-122a, and inferred that DDC is an oncogene. A total of 38 metabolic profiles obtained using LC/MS from the liver tissues of 10 control mice and 10 Mir122a −/− mice were applied to CBM for evaluating similarity ratios between the deficient and normal states.…”
Section: Introductionmentioning
confidence: 99%